Return on investment in workforce development programs - Kevin Hollenbeck (W.E. Upjohn Institute for Employment Research, 2012)
Under more and more fiscal scrutiny because of shrinking state and local budgets, workforce development programs are being asked to estimate their return on investment (ROI). This paper introduces basic concepts of ROI in workforce development programs. It distinguishes ROIs estimated for workforce programs from those that are estimated for financial investments or capital projects. The paper furthermore exposits the basic ingredients of an ROI study - identification of the treatment and time periods of analysis, identification of the net impacts of the program, and identification of net costs. Finally, the paper presents results from the estimation of the ROI for postsecondary career and technical education in the State of Washington.
Keywords: H43; J24; J68; 330; Return on investment; present value; net present value; benefit cost analysis; workforce development; postsecondary CTE; Washington state; human capital